Analisis Alih Kode Pada Tayangan Becanda Tapi Santai Dalam Kanal Youtube Serta Pemanfaatannya Sebagai Media Audiovisual Pada Pembelajaran Teks Anekdot Di Sma Kelas X - Nurdianti, Astri; Nuraini, Cut; Supriadi, Oding (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to describe the forms and causes of code switching found in Becanda Tapi Santai broadcasts on the Youtube channel and its use as an audiovisual medium in teaching anecdotes texts in class X SMA. The research approach is qualitative and qualitative descriptive methods. The subject of this study was the September 2021 issue of Joking But Relaxing through the Trans7 Lifestyle YouTube channel. The results obtained in this study amounted to 50 data. The data is in the form of internal code switching from Indonesian to Javanese totaling 2 data, then external code switching from Indonesian to English and from English to Indonesian totaling 21 data. Meanwhile, the cause of code switching in the form of situations totaling 12 data, 10 data interlocutors, and 5 data topics of conversation, and there is use as an audiovisual media in learning anecdotal texts in class X SMA.